Strategies For Maintaining Quran Memory Through Holiday Classes Management A Case Study At The Muslim Cendekia Institute In Sukabumi - Resi Hanifah; Hadil Ismail Hasan (CV. Edujavare Publishing, 2026)
This research aims to describe the management of the Holiday Halaqah program at Institut Muslim Cendekia (IMC) Sukabumi in maintaining students' memorization quality (itqan) during the academic holiday period. Holidays are often a critical period where students lose their memorization rhythm, necessitating specific management strategies to mitigate this risk. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with 13 informants, participatory observation, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña model. The results indicate that IMC Sukabumi implements four management functions integratively: 1) Planning with differentiated memorization cluster targets; 2) Organizing through a peer-tutoring system by